Standardization of Ukrainian touristic services within framework of European integration - O.V. Milinchuk; Y.O. Kyryjenko (Vìsnik Žitomirsʹkogo Deržavnogo Tehnologìčnogo Unìversitetu: Ekonomìčnì Nauki, 2015)
The harmonization of national standards in tourism to international requirements is a prerequisite to perform in accordance with the signed Ukraine and the European Union Association Agreement. The current situation of the national standardization in tourism and directions of its development in the context of European integration are formed in the article. The content and objectives of standardization in the field of tourism are determined. The legislation of the national tourism standardization is reviewed: there are 11 standards in the field of tourism, including 6 interstate standards (GOST) which adapted as national. The current system of standards has a numerous outdated requirements, Ukrainian enterprises doesn’t use international standards on the organization of trips of adventure tourism, safety management, customer service on cruise ships and ferries, requirements for tourist services etc. In order to satisfy the requirements of quality of tourism services to the European level is recommended to adapt existing ISO standards to the national tourism legislation and to approve them in 2017.